The Influence of Social Structure, Technology, and Background Factors on Supervisory Style in Industry - Chen , Mervin Yaotsu (My University, 1974)
This study was concerned with investigating the causes of supervisory style. To interpret certain dimensions of supervisory style, the superior-subordinate relationship was viewed as a role system. Four dimensions, which are empirically identified but theoretically related to essential conditions of role systems, were investigated: production orientation, worker orientation, closeness, and time allocation. It was argued that while the way a supervisor performs his role may vary along these dimensions, the range of variability is constrained by the social structure and technology of the work place and the background characteristics of the supervisor himself. The general hypothesis of the study was that supervisory style is the product of the interaction of these three factors.
Interviews were conducted with 114 first-line supervisors in seven industries to assess the effect of these factors. A "transitional model" that involved age as a significant variable influencing the closeness of supervision was developed. Three age groups (23-39, 40-49, 50-62) were considered as three periods - initial, transitional, and mature, in correspondence with each age group - which a foreman goes through. In each period the foreman responds to different influencing factors in his environment, so that his supervisory style changes. Two explanations were considered: a "maturational" and a "job security" explanation.
It was also found that most supervisors tend to be almost equally production-oriented and worker-oriented. The nature of production in industry, preference of recruitment, and role conflict experienced by the supervisors were cited as explanations.
Support was found for the hypothesis that time allocation is influenced by technological factors. Planning and the general increment of paper work caused by technological advancement were considered as reasons accounting for this finding.
Keywords: supervisoty style; superior-subordinate; role system